Standardization of Laboratory Methods for the PERCH Study - Driscoll, Amanda J; Karron, Ruth A; Morpeth, Susan C; Bhat, Niranjan; Levine, Orin S; Baggett, Henry C; Brooks, W Abdullah; Feikin, Daniel R; Hammitt, Laura L; Howie, Stephen R C; Knoll, Maria Deloria; Kotloff, Karen L; et al. (Clinical infectious diseases, 2017)
The Pneumonia Etiology Research for Child Health study was conducted across 7 diverse research sites and relied on standardized clinical and laboratory methods for the accurate and meaningful interpretation of pneumonia etiology data. Blood, respiratory specimens, and urine were collected from children aged 1-59 months hospitalized with severe or very severe pneumonia and community controls of the same age without severe pneumonia and were tested with an extensive array of laboratory diagnostic tests. A standardized testing algorithm and standard operating procedures were applied across all study sites. Site laboratories received uniform training, equipment, and reagents for core testing methods. Standardization was further assured by routine teleconferences, in-person meetings, site monitoring visits, and internal and external quality assurance testing. Targeted confirmatory testing and testing by specialized assays were done at a central reference laboratory.